Retinal measurements predict 10‐year disability in multiple sclerosis - Rothman, Alissa; Murphy, Olwen C.; Fitzgerald, Kathryn C.; Button, Julia; Gordon‐Lipkin, Eliza; Ratchford, John N.; Newsome, Scott D.; Mowry, Ellen M.; Sotirchos, Elias S.; Syc‐Mazurek, Stephanie B.; Nguyen, James; Caldito, Natalia Gonzalez; et al. (Annals of Clinical and Translational Neurology, 2019)
Objective Optical coherence tomography (OCT)‐derived measures of the retina correlate with disability and cortical gray matter atrophy in multiple sclerosis (MS); however, whether such measures predict long‐term disability is unknown. We evaluated whether a single OCT and visual function assessment predict the disability status 10 years later. Methods Between 2006 and 2008, 172 people with MS underwent Stratus time domain‐OCT imaging [160 with measurement of total macular volume (TMV)] and high and low‐contrast letter acuity (LCLA) testing (n = 150; 87%). All participants had Expanded Disability Status Scale (EDSS) assessments at baseline and at 10‐year follow‐up. We applied generalized linear regression models to assess associations between baseline TMV, peripapillary retinal nerve fiber layer (pRNFL) thickness, and LCLA with 10‐year EDSS scores (linear) and with clinically significant EDSS worsening (binary), adjusting for age, sex, optic neuritis history, and baseline disability status. Results In multivariable models, lower baseline TMV was associated with higher 10‐year EDSS scores (mean increase in EDSS of 0.75 per 1 mm3 loss in TMV (mean difference = 0.75; 95% CI: 0.11–1.39; P = 0.02). In analyses using tertiles, individuals in the lowest tertile of baseline TMV had an average 0.86 higher EDSS scores at 10 years (mean difference = 0.86; 95% CI: 0.23–1.48) and had over 3.5‐fold increased odds of clinically significant EDSS worsening relative to those in the highest tertile of baseline TMV (OR: 3.58; 95% CI: 1.30–9.82; Ptrend = 0.008). pRNFL and LCLA predicted the 10‐year EDSS scores only in univariate models. Interpretation Lower baseline TMV measured by OCT significantly predicts higher disability at 10 years, even after accounting for baseline disability status.